Germany : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that the financial market turbulence has exposed vulnerabilities in the German financial system. The German consumer's conservatism under the current uncertain conditions will amplify the export slowdown, and investment decisions are likely to be postponed. Executive Directors have welcomed the German authorities' continuing priority to maintain financial stability and stabilize the real economy. Directors have also noted that the global financial crisis has highlighted important vulnerabilities of the German financial system, which could be intensified by the economic slowdown in Germany.